Significações de mulheres pretas inseridas no mundo do trabalho em posições de prestígio social - Santos, Winnie Nascimento dos (2020)
This research investigated the reality of black women inserted in the labor market in positions of social prestige. We sought to analyze their life trajectories and meanings regarding the occupation of this place, where their presence is not expected. Although in a small amount, they are individuals inserted in a challenging context, since they conquer and occupy spaces reserved for white men, within the logic sustained by the subjective dimension of racial inequality. The first chapter of this research explains racism as structuring of the society and subjectivity of the Brazilian people, being this a permanent agent in the history of this country. It also presents the challenges of being a black woman in a class society. The following chapter presents the obstacles that black women face in the labor market, initially elucidating the role of work in a class society, what place these women occupy in this universe, and the trajectory of three notable black women. The third chapter presents the theoretical-methodological framework used for the research, which is developed in the light of socio-historical psychology and historical-dialectical materialism. For this study, interviews were conducted with four black women who occupy managerial positions in various areas of activity: the corporate, academic and political fields. Finally, the final considerations are presented